Deskripsi Model Mental Peserta Didik pada Materi Struktur Atom Fase E SMAN 1 Kubung - Putri Wulandari; Dwi Finna Syolendra (MASALIQ, 2026)
The low achievement in the 2025 senior high school Chemistry Academic Ability Test (TKA) indicates that students’ understanding of chemistry concepts remains suboptimal, particularly in abstract material such as atomic structure, which has the potential to form mental models that are not fully aligned with scientific concepts. This study aimed to describe students’ mental models on atomic structure material in Phase E at SMAN 1 Kubung. This study used a descriptive qualitative approach with 30 tenth-grade students as research subjects. Data were collected through essay tests and interviews. The test instrument was declared valid, with an Aiken’s V coefficient of 0.910. The results showed that students’ mental models were still dominated by the initial model and synthetic model categories, whereas the scientific model category remained relatively low. The interview results showed that students’ mental model patterns were generally consistent between written answers and oral explanations. These findings confirm that students’ mental models on atomic structure material are still at the initial stage to the transition stage toward scientific understanding. The implications of this study indicate the need for chemistry learning strategies that can help students build mental models that are more aligned with the scientific model, particularly in abstract atomic structure material.